Characteristics of Rainfall-Induced Slope Instability in Cisokan Region, Indonesia - Sugeng Krisnanto; Harianto Rahardjo (Journal of Engineering and Technological Sciences, 2021)
A 25.5 km long access road has been constructed in a hilly area in Cisokan region. Several slope instabilities occurred during the rainy season, particularly at the end of heavy rainfall. A comprehensive study was performed to understand the characteristics of rainfall-induced slope instability. The study consisted of field observation, analyses of field and laboratory test data, and numerical analyses. The study revealed that in general there were two categories of slopes with instability characteristics: (i) slopes with a significant groundwater level increase during rainfall; (ii) slopes with an insignificant groundwater level increase during rainfall. In the first category, the slope instability was caused by a loss of matric suction and eventually the pore-water pressure, uw became positive as indicated by an increase of the groundwater level. In the second category, the slope instability was caused by a loss of matric suction without a rise in pore-water pressure, uw, to a positive magnitude. Two empirical curves of slope stability were developed as a preliminary guidance to assess slope stability during rainfall in the region.